OPTIMIZATION OF EXTRACTION AND CROSS-LINKING REACTIONS TO INCREASE THE QUALITY OF HALAL GELATIN FROM SEVERAL TYPES OF FISH - Hamzah, Nursalam
Gelatin is a versatile substance widely used in the medical and pharmaceutical industries for a variety of applications, including capsule shells, X-ray film, plasma substitute infusions, and the fabrication of artificial tissue. Despite its inferior quality, fish scale gelatin is a profitable alternative source of halal material for Indonesia. The addition of crosslinkers can improve the quality characteristics of fish scale gelatin. The aims of the research were to optimize the variables in the base pre-extraction, acid pre-extraction, and gelatin extraction processes to produce gelatin with the most optimum extraction yield. Additionally, it aims to determine quantitative data on the impact of glutaraldehyde, phenolic, and carboxylic acid cross-linkers on the improved character of gelatin, which can be used in the development of capsule shells. Extraction optimization was divided into two stages: selecting the most influential variables using the factorial fraction approach and variable-level optimization using the response surface method approach. Extraction goes through four stages, namely, sorting of raw materials, hydrolysis with alkali and acid, extraction with water, and drying in an oven. In this stage, there are nine variables that influence the extraction process: pre-extraction base concentration, base pre-extraction temperature, base pre-extraction duration, pre-extraction acid concentration, acid pre-extraction temperature, acid pre-extraction duration, temperature extraction, extraction duration, and extraction solvent volume. In the selection stage, four variables were obtained that had a very significant effect, namely pre-extraction base concentration, pre-extraction acid concentration, extraction temperature, and extraction duration (p<0,05). In the level optimization stage, it was found that the optimum extraction soak was obtained if the base concentration was 0,1 N, the acid concentration was 1 N, the extraction temperature was 90 ?C, and the extraction duration varied depending on the sample being examined, namely milkfish (8 hours), snapper (15 hours), and grouper (24 hours). The actual results at the optimum level were close to the predicted results from Milkfish, Snapper, and Grouper, namely 36,3±0,9%, 18,1±0,7%, and 16,1±0,7%, respectively. The addition of crosslinkers can make fish scale gelatin better in terms of its swelling index, degree of crosslinking, viscosity, gel strength, mechanical profile, endothermic peak, and ability to let water vapor pass through. The crosslinkers that were used were glutaraldehyde, phenolic derivative compounds (phenol, pyrocatechol, resorcinol, ?-naphthol, vanillin, L-tyrosine, curcumin, gallic acid, quercetin, and tannic acid), and carboxylic acid derivative compounds (oxalic acid, succinic acid, tartaric acid, phthalic acid, and citric acid). The addition of glutaraldehyde crosslinker (0,5–5%) produced the highest improvement in characteristics, but it carries a risk of toxicity. Tannic acid was a phenolic derivative compound that had the greatest effect on improving marine fish gelatin's characteristics. Making cross-linked gelatin with phenolics was done in a basic environment. Meanwhile, citric acid, a carboxylic acid derivative compound, had the greatest effect on improving the characteristics of fish gelatin. Making crosslinked gelatin using carboxylic acid derivatives requires an acidic environment. Cross-linked gelatin with phenolics at low concentrations can be used to produce capsule shells. Gelatin cross-linked with phenolic at a concentration of 0,5% can dissolve in water so that the capsule shell produced can be destroyed. Crosslinking at moderate concentrations (0,5–2%) can improve the quality characteristics of gelatin. The resulting capsule shell showed a longer disintegration time compared to the blank, which indicated an improvement in gelatin quality.